The Term “Evolution” and its Definition and Use in Czech and British Textbooks of Science and Biology - Müllerová, Lucie (Scientia in educatione, 2015)
The study of evolution and evolutionary mechanisms includes several different approaches. Consequently the concept of evolution is defined in different ways, or is confused with other concepts, such as natural selection or Darwin’s theory. Differences in the use of the terms may result in misconceptions. Therefore, it is necessary to find out, whether textbooks provide space for pupils to orient themselves in the definition of evolution. The research is focused on the occurrence of terms “evolution”, "evolutionary theory”, “biological evolution”, “Darwin’s theory” and “natural selection” in Czech and British textbooks of Science and Biology. There are 32 textbooks included in the survey. The main objective is to determine the frequency of terms mentioned above and subsequently through the content analysis of the definitions to compare the differences in the occurrence of specific predetermined terms. Definition of terms “evolution”, “evolutionary theory” and “biological evolution” are also confronted with the contents of definitions of evolutionary biologists, and their mutual similarity is demonstrated via a hierarchical cluster analysis. The research results indicate that in the Czech textbooks the most prevalent term is “Darwin’s theory” while in British textbooks it is “natural selection”. It has been found that the definitions of “evolution”, “biological evolution” and “evolutionary theory” are quite varied in Czech and British textbooks. Definitions of evolutionary biologists, despite of some variability, are strikingly more similar. Based on the content analysis, such notions are summarized and presented, that seem essential for the understanding of the definition or those that may appear to be a factor influencing the emergence of a pupil’s misconceptions. For the definitions of the term “evolution” it is found, that the Czech textbooks describe the “evolution” mostly as “the development of organisms” or “the origin of new species”. British textbooks primarily contain “change of organisms over time”, and the definition of evolutionary biologists usually involves “changing the genes in the population”.